Effect of Pressure-controlled intermittent Coronary Sinus Occlusion (PiCSO) on infarct size in anterior STEMI: PiCSO in ACS study. (June 2020) - Egred, Mohaned; Bagnall, Alan; Spyridopoulos, Ioakim; Purcell, Ian F.; Das, Rajiv; Palmer, Nick; Grech, Ever D.; Jain, Ajay; Stone, Gregg W.; Nijveldt, Robin; McAndrew, Thomas; Zaman, Azfar
Highlights: STEMI patients treated with PiCSO were propensity matched to INFUSE-AMI controls. Infarct size at day 5 was significantly lower in the PiCSO group. There were no major adverse cardiac events (MACE) related to the PiCSO. Abstract: Background: The aim of this clinical research was to investigate the effects of Pressure-controlled intermittent Coronary Sinus Occlusion (PiCSO) on infarct size at 5 days after primary percutaneous coronary intervention (pPCI) in patients with ST-segment elevation myocardial infarction (STEMI). Methods and results: This comparative study was carried out in four UK hospitals. Forty-five patients with anterior STEMI presenting within 12 h of symptom onset received pPCI plus PiCSO (initiated after reperfusion; n = 45) and were compared with a propensity score-matched control cohort from INFUSE-AMI (n = 80). Infarct size (% of LV mass, median [interquartile range]) measured by cardiac magnetic resonance (CMR) at day 5 was significantly lower in the PiCSO group (14.3% [95% CI 9.2–19.4%] vs. 21.2% [95% CI 18.0–24.4%]; p = 0.023). There were no major adverse cardiac events (MACE) related to the PiCSO intervention. Conclusions: PiCSO, as an adjunct to pPCI, was associated with a lower infarct size at 5 days after anterior STEMI in a propensity score-matched population.